Farhana Environmental Scientist receives Royal Education Award Pingat Jaya Cemerlang - Halizan, Mohmood; Nur Hartini, Mohd Hatta (UMPSA, 2022)
KUANTAN, 6 August 2022 - Farhana Munirah Zainuri, the daughter of Zainuri Mohd Shafar, 51, and Zainatunakmar Abdul Manap, 49, is the eldest of three siblings who received the dean’s list certificate every semester and completed her degree in Bachelor of Engineering Technology (Energy and Environment) with Honours at Universiti Malaysia Pahang (UMP) with a CGPA of 3.82.